Aircraft Systems Integration of Air-Launched Weapons - Rigby, Keith A (Aerospace Series, 2013)
From the earliest days of aviation where the pilot would drop simple bombs by hand, to the highly agile, stealthy aircraft of today that can deliver smart ordnance with extreme accuracy, engineers have striven to develop the capability to deliver weapons against targets reliably, safely and with precision.Aircraft Systems Integration of Air-Launched Weaponsintroduces the various aspects of weapons integration, primarily from the aircraft systems integration viewpoint, but also considers key parts of the weapon and the desired interactions with the aircraft required for successful target engagement.Key features:Addresses the broad range of subjects that relate directly to the systems integration of air-launched weapons with aircraft, such as the integration process, system and subsystemarchitectures, the essential contribution that open, international standards have onimproving interoperability and reducing integration costs and timescalesDescribes the recent history of how industry and bodies such as NATO have driven the needfor greater interoperability between weapons and aircraft and worked to reduce the cost andtimescales associated with the systems integration of complex air-launched weapons withaircraftExplores future initiatives and technologies relating to the reduction of systems integrationcosts and timescalesThe systems integration of air-launched weapons with aircraft requires a multi-disciplinary set of engineering capabilities. As a typical weapons integration life-cycle spans several years, new engineers have to learn the skills required by on-the-job training and working with experienced weapons integrators. Aircraft Systems Integration of Air-Launched Weaponsaugments hands-on experience, thereby enabling the development of subject matter expertise more quickly and in a broader context than would be achieved by working through the life-cycle on one specific project. This book also serves as a useful revision source for experienced engineers in the field.